The nephroprotective effects of Daucus carota and Eclipta prostrata against cisplatin-induced nephrotoxicity in rats. Issue 2 (20th December 2021) - Iqbal, Muhammad Omer; Sial, Asad Saleem; Akhtar, Imran; Naeem, Muhammad; Hazafa, Abu; Ansari, Rais A.; Rizvi, Syed A. A.
ABSTRACT: The overuse of cisplatin (>50 mg/m 2 ) is limited to nephrotoxicity, ototoxicity, gastrotoxicity, myelosuppression, and allergic reactions. The objective of this study was to investigate the nephroprotective effects of Daucus carota and Eclipta prostrata extracts on cisplatin-induced nephrotoxicity in Wistar albino rats. The study involved male Wistar albino rats of 8 weeks weighing 220–270 g. A single injection of 5 mg/kg was injected into the rats for nephrotoxicity. Rats were divided into four groups based on dose conentrations. Blood and urine samples of rats were collected on the 0, 7 th, 14 th, and 21 st days for nephrological analysis. The results showed that Cis + DC/Cis + EP (600 mg/kg) significantly (p < 0.001) increased the body weight and reduced the kidney weight of cisplatin-induced nephrotoxicity in rats (p < 0.001) as compared to Cis group. The results showed that 600 mg/kg administration of Cis + DC/Cis +EP successfully (p < 0.005) improved the urine and plasmin creatinine, Na, and K level compared to the Cis group. Histopathological results confirmed that Cis + EP/Cis + DC effectively improved the renal abnormalities. It is concluded that the co-administration of Cis + EP extract showed exceptional nephroprotective effects at a dose rate of 600 mg/kg.